Juridical Analysis of Difference in the Supreme Court’s Decision About the Validity of the Land Sale and Purchase Under Private Agreement - Futuhatul Magfirah; Mohammad Jamin (GoAcademica Research & Publishing, 2022)
The research aims to determine the causes of differences in Supreme Court judges' decisions at the cassation and judicial review levels, to identify Supreme Court judges' decisions at the Review level regarding the invalidity of the private land sale and purchase agreement in case number 833/PK/Pdt/2018 from the perspective of contract law as prescribed by the Civil Code. It is a normative or doctrinal juridical legal research using a statute approach, a case approach, and a conceptual approach. The results obtained first, the reason for the difference between the Supreme Court's decisions is from the point of view of the judge's legal considerations. Second, the Supreme Court's Decision Number 833/PK/Pdt/2018, which declares that the Sale and Purchase Agreement is invalid and declared null and void based on the Civil Code, is incorrect. But, as stated in Article 1334 of the Civil Code, the agreement is void because the object of the agreement is an unopened inheritance.